MEMORIZING PROPAGANDA OF EQUALITY IN NGULANDARA AND KIRTI NDJOENJOENG DRADJAT, NOVELS OF BALAI POESTAKA (Mengingat Kembali Propaganda Kesetaraan dalam Novel-Novel Balai Poestaka, Ngulandara dan Kirti Ndjoenjoeng Dradjat) - Yohanes Adhi Satiyoko (Kandai, 2020)
Equality of men is a great issue to maintain every country all the time. Indonesia is one of them which should struggle to maintain it so far. Fictional work is one of the aesthetical means to support it. The way of struggle can be memorized through the time of independence era in fictional works of Balai Poestaka publisher. Javanese language novels, Ngulandara and Kirti NdjoendjoengDradjat are two literary works published by BalaiPoestaka that were written in the dominance times of Balai Poestaka activities as commission for people’s reading in Dutch colonial era in Indonesia (Dutch Indies). Kepriyayian (nobility) was the theme of Ngulandara (1936) and Kirti NdjoendjoengDradjat(1924) novels. As seen from propaganda point of view, ideologically the portrayal of priyayi (nobleman) was analogy symbol of Dutch colonial government that ruled social system. Ngulandara and Kirti Njunjung Drajat showed a “struggle” through literary works as portrayed in wong cilik (Javanese: lower class people) who struggled against the existence of the authorities. The struggle emerged in the way of wong cilik behaved intellectually, morally, even mannerly better than the nobles (priyayi). This research used the theory of literature and propaganda using a sociological approach. Those oppositional relationships between deconstruction nobles and the raise of wong cilik in the field of intellectual, moral, and manner show the propaganda of equality of men through the voice of Jasawidagdo and Margana Djajaatmadja.Kesetaraan manusia merupakan isu besar yang harus selalu dijaga di setiap negara. Indonesia adalah salah satu negara yang harus tetap berjuang menjaga isu tersebut. Karya fiksi berfungsi sebagai salah satu peranti estetis untuk mendukung isu tersebut. Cara memperjuangkan isu tersebut ialah dengan mengingat kembali masa kemerdekaan melalui penerbit Balai Poestaka. Novel-novel berbahasa Jawa, Ngulandara dan Kirti Ndjoendjoeng Dradjat ialah dua karya sastra yang diterbitkan oleh Balai Poestaka yang ditulis pada waktu dominasi Balai Poestaka sebagai komisi bacaan rakyat di era kolonial Belanda di Indonesia (Hindia Belanda). Kepriyayian merupakan tema novel Ngulandara (1936) dan Kirti Njoendjoeng Dradjat (1924). Dilihat dari sudut pandang propaganda, penggambaran priyayi merupakan analogi simbol pemerintah kolonial Belanda yang berkuasa mengatur sistem sosial kemasyarakatan. Ngulandara dan Kirti Ndjoendjoeng Dradjat menunjukkan sebuah “perjuangan” melalui karya sastra seperti digambarkan melalui wong cilik yang berjuang melawan kemapanan penguasa. Perjuangan tersebut muncul dengan cara wong cilik tersebut bertindak secara intelektual, bermoral, bahkan bersikap lebih terhormat daripada para priyayi. Penelitian ini menggunakan teori sastra dan propaganda dengan pendekatan sosiologi. Relasi oposisional antara dekonstruksi priyayi dan bangkitnya wong cilik dalam ranah intelektual, moral, dan sikap menunjukkan propaganda kesetaraan manusia melalui suara Jasawidagdo dan Margana Djajaatmadja.